2018
DOI: 10.3126/njog.v12i1.18981
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum Hysterectomy and Analysis of Risk Factors

Abstract: Aims:To determine the incidence and risk factors of women undergoing peripartum hysterectomy at BPKIHS, Dharan.Methods: A descriptive study was conducted for all women undergoing peripartum hysterectomy in two years from July 2012 to June 2014.Various maternal characteristics including demographic data, previous obstetric details, antepartum, intrapartum and postpartum data were collected and analysed.Results: There were 29 cases of peripartum hysterectomy among 19,539 births in 2 yrs (1.48 per 1000 births). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A similar study showed an incidence of 1.48 per thousand which was higher than our study. 11 Our study showed the main indication of EPH was placenta accreta spectrum 62.5% followed by uterine atony 32.5% but another study showed rupture uterus was the common indication. 11 Several studies have shown that abnormal placentation is the major cause of EPH, replacing uterine atony.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…A similar study showed an incidence of 1.48 per thousand which was higher than our study. 11 Our study showed the main indication of EPH was placenta accreta spectrum 62.5% followed by uterine atony 32.5% but another study showed rupture uterus was the common indication. 11 Several studies have shown that abnormal placentation is the major cause of EPH, replacing uterine atony.…”
Section: Discussionmentioning
confidence: 49%
“…Another study showed three mortality due to haemorrhagic shock. 11 In another study showed there was no mortality death report. 14 …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The main reason being unbooked cases, obstructed labour and previous cesarean section. 20,21 Whereas in some center, in Nepal and Egypt the primary indication is uterine atony. 11,22 EPH is a massive challenge to the obstetrician and anesthesiologist.…”
Section: Discussionmentioning
confidence: 99%